Developing a scientific practice in preservation of 19th century Royal Malay songket shawl - Janpourtaher, Mina; Barkeshli, Mandana; Othman, Rashidi (Science Publishing Group, 2019)
The fabric under study is one of the exquisite songket shawl dated around 19th century housed in National Museum of Malaysia. This study aims to identify the materials, techniques and analyze the texture, motifs and dyes through historical and artistic review as well as scientific analysis, identification of deterioration factors and examining the different causes of damages. In order to conserve and restore the samples, identification of the material technology on natural and metal threads, weaving as well as dye and motifs were carried out. Natural fibers were detected by using chemical analysis, FTIR and FESEM-EDS were used for examination of metallic threads. The condition survey was carried out and analyzed through the original historic samples to identify its feature and behavior against physical and chemical agencies. Examination results showed the fibers are delicate cotton and natural pigments used in dying process. Also according to the FESEM results, metal threads was identified as gilt-silver which is deteriorated in some parts and covered with layer of corrosion. A series of internal and external destructive factors as well as improper past repairs caused several damages to the fabric. It became evident that by exposing fabrics to improper storage and display technique had caused considerable physical, chemical and mechanical harm to the parts of sample. Based on the current condition of the fabric proper method of preservation treatment was applied and a specific method of displaying of songket shawl textiles was designed as a guideline for Malaysia’s museums.